Analysis of Marketing Mix Strategies to Increase Export Sales Volume in The Kawoel’s Coir Pot Industry - Saputra, Dicky Permadi; Sardanto, Rino (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: The aim of this research is to determine the application of the 7P marketing mix used by the Kawoel's industry to increase the export sales volume of coir pot products. Design/Method/Approach: The type of research used is descriptive research using a qualitative approach. The method used in collecting data is observation, interviews and documentation to describe the industrial situation in its operations. The sources in this research are owners, employees and customers. Research Finding: The research results show that the 7P strategy (product, price, place, promotion, people, Physical Evidence, Process) has been successfully implemented in Kawoel's industry. These products are sold with good quality and contemporary designs. The prices applied are in accordance with the quality provided. The location used is to analyze the market potential of the export destination country. Promotion utilizes social media WhatsApp and Instagram as a tool to market products. This industry has employees who are friendly to consumers so they can serve customers well. Kawoel's industry has raw material suppliers so that making its products does not require a long time and already has adequate tools and facilities so that it can help to increase export sales of coir pots. Kawoel's industry should prioritize which countries have great opportunities and leverage e-commerce platforms and social media applications to increase sales. Theoretical Contribution/Originality: The 7P marketing mix helps the industry more comprehensively design marketing strategies to create a better customer experience. Practitioner/Policy Implications: The 7P marketing mix involves product, price, place, promotion, people, processes and physical evidence so it is necessary to understand how each element can influence business performance and meet customer needs. Research Limitations:This research only focuses on marketing which is used to increase export sales.